2019
DOI: 10.29252/ijree.4.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Speaking Activities on Iranian Intermediate EFL Learners’ Oral Performance

Abstract: This study aimed to investigate the impact of pre-speaking activities on Iranian intermediate English as a Foreign Language (EFL) learners' oral performance. The study followed a quasi-experimental design in which subjects of the study were non-randomly selected. Oxford Placement Test (OPT) was used to select 100 intermediate EFL learners as the main sample. Then they were divided randomly into two experimental and control groups. Prior to the treatment, participants of both groups were given a pretest of spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…According to Dabiri and Pourhosein Gilakjani (2019), while young language learners acquire foreign languages more easily and quickly, adults are motivated to develop language abilities and achieve new proficiency. However, many adults fail to achieve native-like proficiency due to "fossilization," which affects prosodic features such as intonation, stress, and rhythm.…”
Section: Nature Of Speakingmentioning
confidence: 99%
“…According to Dabiri and Pourhosein Gilakjani (2019), while young language learners acquire foreign languages more easily and quickly, adults are motivated to develop language abilities and achieve new proficiency. However, many adults fail to achieve native-like proficiency due to "fossilization," which affects prosodic features such as intonation, stress, and rhythm.…”
Section: Nature Of Speakingmentioning
confidence: 99%
“…That's right, and college students need classroom communication activities to practice speaking English and improve speaking as well as other language learning skills. Dabiri (2019) said that speaking practice in class is an opportunity to develop students' speaking skills that they are always encouraged to participate in class activities to express their views and ideas. So, teachers should organize a lot of interactive tasks/ activities in the classroom to create an English practice environment for students.…”
Section: Clt Strategies To Improve English Speaking Skills Classroom ...mentioning
confidence: 99%
“…So, wherever possible, students have to speak English with some friends and teachers who will or can speak English with. Dabiri (2019) said that speaking practice in class is an opportunity to develop students' speaking skills that they are always encouraged to participate in class activities to express their views and ideas.…”
Section: Enhancing Media On Clt Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Meena (2020) has emphasized the need to form cooperative learning groups to teach the English language or to improve the communication skills of the students so that the teachers of higher education cannot find any linguistic barrier in interacting with the students. Dabiri and Gilakjani (2019) concluded that the statistical significance of pre-task planning in teaching EFL learners where the pre-task planning aided in diminishing the syntactic and grammatical complexities. In this study, a pre-and post-test was conducted to evaluate the effectiveness of pragmatic and targeted tasks that were found to be effective in instilling linguistic skills among the students of EFL (Chen, 2020).…”
Section: Introductionmentioning
confidence: 99%